A gyermekek szegénysége - Darvas, Ágnes; Tausz, Katalin (Szociológiai Szemle, 2024)
We investigated the poverty of children by means of a sample covering only the poorest third of the population. Our starting point was that children have special needs that differ from those of adults, and that the degree of satisfaction of those needs determines to a large extent the quality of their life and their future life chances. The results show that within the poor population the children in the most disadvantaged situation are those who live in Budapest, who live in families without an active earner, and the children of the Roma. The difference between the poverty of children living in the capital and in villages is significant despite the fact that on the national level the income level of the capital is higher than in the villages. Two factors that were expected to be significantly influencing need satisfaction, namely the age of the children and the number of children in the household do not seem to differentiate significantly the poor population. The majority of poor households with children get some social benefits but the level of the benefits is too low to significantly improve the situation.